Educational intervention in caregivers to prevent pressure ulcers in adults with prolonged immobility - Morales Castillejos, Lizbeth (Universidad de Sonora, 2020)
Introduction: The knowledge of caregivers about the prevention of pressure ulcers in patients with immobility is useful to prevent the appearance of injuries, by means of planning, implementing, and assessing of an at-home educational program. Objective. To determine the efficiency of educational intervention about knowledge regarding prevention of pressure ulcers in primary caregivers of patients with prolonged immobility. Methodology: A quasi-experimental design and simple random sampling; the intervention group was considered as its own control under a test and re-test statistical treatment, with simple blind intervention to 15 caregivers of adult patients, hospitalized with indication of discharge and in risk of suffering pressure ulcers. The intervention was implemented in three phases of four sessions conducted as a workshop, with duration of thirty minutes. Data analysis was descriptive, and in order to compare the test and re-test a Student’s t-test was applied. Ethical issues were considered for a low-risk survey. Results: In the diagnosis phase 80% of caregivers had no knowledge at all, in the re-test 100% of them increased knowledge with a positive and significant effect (p=.000). Conclusion. The result obtained showed statistically significant efficiency of the four sessions that comprised the educational program to increase the level of knowledge of caregivers for the prevention of pressure ulcers.